Microeconomics - Roger A. Arnold (South-Western/Cengage Learning, 2008)
This engaging text continues to set the standard for clear, balanced, and thorough coverage of the principles of economics. Packed with intriguing pop culture examples, it bolsters student interest by illustrating the unexpected places economics occurs, and how economic forces link events to our lives. With new content reflecting a changing economy and new resources addressing the needs of a changing classroom, MICROECONOMICS, 9e is an ideal solution for Principles courses